Global trends in cervical spondylosis research: a bibliometric analysis based on the Web of Science - Jiang, Lin; Xu, Yu; Yang, Zhijun; Li, Penghui; Dong, Youkang; Yang, Guangzhi (Frontiers in Neurology, 2025)
ObjectiveWe aim to analyze the development trends in cervical spondylosis research and guide future studies. Cervical spondylosis, a standard neck disorder characterized by pain, nerve compression, and spondylosis, is highly prevalent, particularly among older individuals, due to the extensive use of electronic devices. Since treatment options are limited and surgery is considered a last resort, it is crucial to explore the current research status and identify areas for further investigation.MethodWe conducted a bibliometric analysis of academic articles on cervical spondylosis published between 1980 and 2022. The analysis involved utilizing the Web of Science database and employing R software and a VOS viewer.ResultsOur analysis revealed that neurosciences and neurology were the primary research focus, with participation from 62 countries. China had the highest number of publications, while the USA received the most citations. The Rothman Institute emerged as the most cited institution in neck pain research. The journal “Spine” had the highest publication count. Among authors, Mummaneni P. V. was the most cited, and Liu H. had the highest number of publications. The keyword “Spine” was the most frequently used.ConclusionOur bibliometric study summarized the current research status of cervical spondylosis. Further investigations are warranted in diagnosis, treatment, prevention, non-surgical interventions, and rehabilitation. Promising areas of interest include artificial cervical discs, gene therapy, and stem cell therapy. Our study provides a framework for enhancing cervical spondylosis’s diagnosis and treatment by addressing existing literature gaps.